DIFERENSIASI AL-TAWARRUQ AL-MASRAFI DAN AL-TAWARRUQ AL-FIQHI MENURUT HUKUM EKONOMI SYARIAH - Robbani, Shofa (Universitas Nahdlatul Ulama Sunan Giri, 2021)
Abstract: The practice of the bai' al-tawarruq contract has existed since the era of the four mujtahids, it's just that the term bai' al-tawarruq only appeared in the Middle Ages, the first person to mention the term bai' al-tawarruq was a Hanbali scholar, Ibn Taimiyah. In the modern era, this term has been divided by the practice carried out in Islamic banks called bai' al-tawarruq al-masrafy and those carried out outside Islamic banks called bai' al-tawarruq al-fiqhi. These two types of bai' al-tawarruq contracts look the same in practice as bai' al-'inah but have differences with the involvement of third parties in the practice of bai' al-tawarruq, which is not present in bai' al-'inah. The pros and cons of Ulama against the law of bai' al-tawarruq have existed since the classical era, the majority of Ulama of the three madhhabs (Hanafi, Maliki, and Shafi'i) prohibit the practice of bai' al-tawarruq on the grounds of hailah and leads to usury, only the Hanbali madhhab is driven by Ibn Taimiyah and Ibn al-Qayyim who allowed the contract with the argument that bai' al-tawarruq was different from the forbidden bai' al-'inah contract. Meanwhile, contemporary scholars have different opinions in punishing bai' al-tawarruq al-masrafy. Referring to the results of the congress and conference decisions in Sharjah, United Arab Emirates, Bahrain, and Saudi Arabia in 1423 H. There were two opposing camps in formulating the law of bai' al-tawarruq al-masrafy. The first camp, the majority madhhabs forbids financial transactions using this contract in Islamic banks because it contains elements of usury, hailah and includes the form of bai' al-'inah. While the second camp, minority madhhabs tend to allow it for reasons of emergency and urgent need as well as to fulfill liquidity.